Pengembangan Desain Interior Pasar Daerah Indramayu Dengan Pendekatan Sense Of Place - Putra Pratama, Calvine; Nur Sheha Gunawan, Ahmad; Primiana Yuniati, Arnanti (eProceedings of Art & Design, 2024)
Markets usually consist of stalls or outlets, los, and open-air markets opened by sellers and market managers. A market is also a place where sellers and buyers meet and where direct sales transactions of goods take place. The market consists of various potential customers with similar needs and wants. Among these, regional markets or traditional markets are types of markets that are divided into two based on transaction volume and size. Modern markets such as minimarkets, hypermarkets, and malls are gradually replacing traditional markets due to the phenomenon that occurs in big cities today. Since modern markets are more convenient and clean, people prefer to shop in modern markets. With this advancement in market interior design. Keywords: market, convenience, visitor interest